PENGARUH WORK FROM HOME DAN WORK LIFE-BALANCE TERHADAP WORK ENGAGEMENT DENGAN JOB SATISFACTION SEBAGAI PEMODERASI PADA WORK ENGAGEMENT KARYAWAN PT. BANK CENTRAL ASIA TBK SAAT PANDEMI COVID-19 - Pujiati, Devi; Emilisa, Netania; Romadhania, Nurizahara (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Since December 2019, the coronavirus (COVID-19) has spread rapidly on a global scale, severely affecting organizations from all sectors of activity. A banking employee is someone who is in charge of handling customers, seeking incoming funds, offering credit and bank products. Therefore, to ensure the job satisfaction of bank employees. The purpose of this study was to examine the effect of working from home and work-life balance on job satisfaction and bank employee job involvement. The survey resulted in 150 respondents. The method used to analyze this research is instrumental tests such as validity, reliability, and hypothesis testing using SPSS version 22 and SEM analysis. This study explores the perceptions of employees working at PT. Bank Central Asia Tbk to verify the validity and reliability of research instruments. The results of the study show that working from home has a positive effect on job satisfaction, work-life balance has a positive effect on job satisfaction, job satisfaction has a positive effect on work involvement.